Deep tissue blood perfusion assessment using diffuse speckle contrast analysis : a validation study - Lin, Nanda Myaing (2014)
Non-invasive blood flow measurement in deep tissue level is critical for the clinical blood perfusion assessment during angioplasty procedure. An emerging modality for non-invasive deep tissue blood flow monitoring would be the Diffuse Correlation Spectroscopy (DCS). Nonetheless Diffuse Speckle Contrast Analysis (DSCA) is developed as an alternative approach towards the noninvasive and efficient assessment of blood perfusion rate in real time monitoring. DSCA is the incorporated modality, based on the principle of DCS and analysis of Laser Speckle Contrast Imaging (LSCI). DSCA offers the cost effective and real time measurement compared to the existing DCS modality.